Wireless power transmission for remote‐relay‐nodes‐aided smart metering. Issue 16 (5th February 2019) - Wang, Qing; Dai, Yanjie; Du, Yan; Li, Xiao; Li, Fucun; Wang, Lingyin
Abstract : Wireless power transmission is a promising technique to provide continuous power supply for the limited capacitance of smart meters (SMs) with short distance communication. In this study, the authors propose a remote‐relay‐nodes (RRNs)‐aided wireless SM system, where several geographically separated RRNs are connected to a concentrator or an acquire terminal via radio‐over‐fibre. A RRN selection scheme is employed in the wireless power transfer phase. With the energy harvested, the SM can report special or urgent events in the wireless information transfer phase. The asymptotic reporting probability and reliability of smart metering are derived in terms of close form over fading channels. Numerical results are provided to verify the theoretical analysis. The optimal deployment of RRNs can be also efficiently obtained by averaging the locations of a SM in the network.